Interesting new Chinese species of Leptoceridae and Odontoceridae (Insecta: Trichoptera) from several recent collecting efforts - Yang, Lian-Fang; Hu, Ben-Jin; Morse, John C. (Zootaxa, 2020)
In contravention of Article 16.4.2 of the International Code of Zoological Nomenclature (International Trust for Zoological Nomenclature 1999), the repository for the holotypes of these species was not mentioned by Yang et al. (2020), such that the names proposed for these species are presently nomina nuda.